Comment on ‘‘Stratigraphy of the Northern Pulo do Lobo Domain, SW Iberia Variscides: A palynological contribution’’ by Zelia Pereira et al. (2018) – Geobios 51, 491–506 - Pereira, Manuel Francisco (2019)
The paper by Zelia Pereira et al. (2018) is a valuable input to better constrain the Devonian palynological record of a number of siliciclastic formations of the Pulo do Lobo Unit (also known as Pulo do Lobo Domain or Pulo do Lobo Zone) in SW Iberia. They have recognized for the first time in the Pulo do Lobo Fm. and in the imbricated phyllites of the Peramora Me´lange palynomorph assemblages assigned to the middle Frasnian, as well as new Devonian palynomorphs in the Ribeira de Limas, Santa Iria and Horta da Torre formations, and the Alajar Me´ lange. Furthermore, Ze´ lia Pereira et al. (2018) intend to promote a ‘‘detailed discussion of the palynological versus geochronological ages by comparing their biostratigraphic ages with the maximum depositional ages inferred for the same formations according to detrital zircon geochronology (Pe´rez-Ca´ ceres et al., 2017; Pereira et al., 2017). The purpose of their discussion is to question the validity of zircon geochronological data, which allegedly would be contradictory with the palynomorph content, and thus not compatible with the established stratigraphic sequence. In our view, this discussion is inconsistent due to: i) the impossibility that primary igneous ages in zircon grains would have been rejuvenated during Early Carboniferous low- grade regional metamorphism; ii) a wrong interpretation of the meaning and implications of maximal depositional ages derived from the youngest detrital zircon population.